Determination of Fertilizer Doses of Sweet potato (Ipomoea batatas L.) “Rancing” - Ayu Puspita Ningrum; Suwarto Suwarto; Asep Setiawan (Journal of Tropical Crop Science, 2018)
Nitrogen, phosphorus, and potasium availability are the most thresholding factors for maximum growth and yield. The tuber yield of sweet potato varies depending on growing area therefore a fertilization program, especially in the type and the dose of the fertilizers, is required. This research was conducted in the Pasir Muncang experimental farm at Gadog, Bogor, West Java, Indonesia. The study site is located ±500 meters above sea levels, 6°39’31.90” south latitude and 106°52’7.77” east longitude. The experiment was started in May to September 2017. Multi nutrient response method was used for this study, and the interpretation of the results was used to develop fertilizer recommendations using single-nutrient quadratic model. The recommendation was determined using N, P2O5, K2O fertilizer response curve, where the first recommendation was calculated from the maximum relative yield,and the second, third, and fourth recommendation were determined from N, P2O5, K2O threshold. Each treatment for N, P and K was evaluated with different level of fertilizer dose using a randomized complete block design with three replications. The fertilizer doses were 50, 100, 150 and 200% from reference (100% N = 100 kg N ha-1, 100% P = 75 kg P2O5 ha-1, dan 100% K = 100 kg K2O ha-1). Relative yield of sweet potato (y), response to fertilizer (x) had improvement quadratically with equation y = -0.0017x2 + 0.538x + 40.035 for N, y = -0.0041x2 + 0.8595x + 38.211 for P2O5, and y = -0.0025x2 + 0.4318x + 73.377 for K2O. The optimized dose of fertilizer to get maximum yield of sweet potato tuber is 158.23 kg ha-1 of N, 78.60 kg ha-1 of P2O5, and 83.60 kg ha-1 K2O, or 343.97 kg ha-1 of Urea,  218.53 kg ha-1 of SP36 139.33 kg ha-1 of KCl.Keywords: multi nutrient response, nitrogen, relative yield, phosphorus, potassium